2019
DOI: 10.21873/anticanres.13929
|View full text |Cite
|
Sign up to set email alerts
|

Further Quantitative Structure–Cytotoxicity Relationship Analysis of 3-Styrylchromones

Abstract: Background/Aim: Very few studies are available about the biological activity of 3-styrylchromones. Our previous study demonstrated the importance of methoxy group at 6-position of the chromone ring and hydroxyl group at 4'position of phenyl group in styryl moiety. As a sequel of this study, we synthesized fourteen compounds that include eight 3-styrylchromones where methoxy group was introduced at 7position of chromone rings, and then evaluated their tumorspecificity. Materials and Methods: Tumor-specificity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 10 publications
4
34
0
Order By: Relevance
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
“…This demonstrated that only limited numbers of compounds show higher tumor specificity, although their structures are very similar with each other. It is possible that such highly tumor-specific compounds show the optimal 3D structure, since the tumor specificity of chromone compounds shows the tight correlation with chemical descriptors that reflect the 3-D structure ( Table 4 ) [ 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Opti-MEM ® and Mouse IL-6 Uncoated ELISA Kit were purchased from Thermo Fisher Scientific (Waltham, MA, USA). 2) were synthesized by Knoevenagel condensation of the appropriate 3-formylchromone with selected phenylacetic acid derivatives, as described previously [42,44]. All the compounds were characterized by 1 H NMR, MS spectra and elemental analyses after purification by silica gel column chromatography and recrystallization.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…As stated, the HMGB1-RAGE axis in TME is closely associated with carcinogenesis; thus, anti-cancer compounds targeting this axis that possess further anti-inflammatory activity may have far-reaching therapeutic potential. In this study, four 6-methoxy-3-styrylchromone (6M3SC) derivatives, which have already identified as anti-cancer agents [41][42][43][44], were selected by a papaverine 3D pharmacophore similarity search and examined in terms of their anti-inflammatory activities by a cell-based inflammatory assay method driven by the HMGB1-RAGE-mediated system using macrophage-like RAW264.7 cells. This research is the first to demonstrate a unique 6-methoxy-3-hydroxy-styrylchromone (compound 3, 6M3HSC) that has both potent anti-cancer and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%